Comparative Proteomics Reveals Dysregulated Mitochondrial O-GlcNAcylation in Diabetic Hearts - Ma, Junfeng (J Proteome Res, 2016)
O-linked β-N-acetylglucosamine (O-GlcNAc), a post-translational modification on serine and threonine residues of many proteins, plays crucial regulatory roles in diverse biological events. As a nutrient sensor, O-GlcNAc modification (O-GlcNAcylation) on nuclear and cytoplasmic proteins underlies the pathology of diabetic complications including cardiomyopathy. However, mitochondrial O-GlcNAcylation, especially in response to chronic hyperglycemia in diabetes, has been poorly explored. We performed a comparative O-GlcNAc profiling of mitochondria from control and streptozotocin (STZ)-induced diabetic rat hearts by using an improved β-elimination/Michael addition with isotopic DTT reagents (BEMAD) followed by tandem mass spectrometric analysis. In total, 86 mitochondrial proteins, involved in diverse pathways, were O-GlcNAcylated. Among them, many proteins have site-specific alterations in O-GlcNAcylation in response to diabetes, which suggests that protein O-GlcNAcylation is a novel layer of regulation mediating adaptive changes in mitochondrial metabolism during the progression of diabetic cardiomyopathy.